Sanal kütüphane sistemleri - Acar, Arzu (My University, 2004)
By the development of information technology, forms and functions of libraries change and libraries gain new shapes, forms and functions. People are always in need of information, which is provided by others for different reasons. However, the ways of presentation of information and methods of usage of it are under the influence of technology. That has created the change in the library systems. In light of thse developments, together with the classical libraries, by the use of Internet, e-libraries, on-line databases, e-books, e-journals and digital libraries have occupied significant place in providing information. In this project, all these forms of libraries have been elucidated and a digital library system has been into practice. As a result of this research, it is expected that libraries will be used progressively and continuously and they will bu used widely in the future. However, it would a false statement to argue for digital libraries to take place classical libraries in the future. To obtain all these information forms which technology presents humanity and the proper and efficient use of them will clarify the way we lokk at information technology and will be influentail on the discussions toward where the change will be directed. Adı ve Soyadı: Arzu Acar letişim Bilimleri Yrd. Doç. Dr. Cem S. Sütçü Tez Türü ve Tarihi: Yüksek Lisans - Aralık 2004 stemleri, Kütüphane, Sanal Kütüphane, Elektronik Kütüphane

SANAL KÜTÜPHANE SİSTEMLERİ Bilişim teknolojisinin ilerlemesiyle kütüphanelerin biçimleri ve işlevleri değişmiş ve gelişmiştir. İnsanların, başkaları tarafından yaratılan bilgiye, çeşitli amaçlarla her zaman gereksinimleri vardır. Ancak, bilginin sunuluş biçimleri ve bilgiyi kullanış yöntemleri teknolojinin etkisindedir. Değişimi yaratan da budur. Bu gelişmeler ışığında artık klasik kütüphaneler dediğimiz kütüphanelerin yanında internetle birlikte elektronik kütüphaneler, veri tabanları, e-kitaplar, e-dergiler ve sanal kütüphaneler bilgi gereksiniminin karşılanmasında önemli bir yer tutmaktadır. Bu çalışmada tüm bu türler incelenmiş ve bir sanal kütüphane uygulaması yapılmıştır. Uygulama sonucunda sanal kütüphanelerin hızla ilerleyerek kullanılacağı ve yaygınlaşacağı ancak bunun klasik kütüphanelerin yerini almayacağı öngörülmüştür. Teknolojinin insana sunduğu tüm bu bilgi anahtarlarını elde etmek ve bunlara doğru zamanda gerektiği kadarıyla kullanmak bilişim teknolojisine bakış açısını netleştirecek ve değişimin hangi yöne doğru evrileceği noktasında yapılan tartışmalarda etkili olacaktır.
Keywords: Kütüphane Sistemleri